Analisis Efisiensi Industri Manufaktur Besar dan Sedang di Provinsi Jawa Barat - M. Mujiya Ulkhaq (Penerbit Goodwood, 2023)
Purpose: This study aims to analyse technical efficiency of large and medium manufacturing industries (LMMIs) in West Java Province, Indonesia. Method: The slacks-based measure (SBM) of efficiency in data envelopment analysis (DEA) is used to accomplish the objective of the study. The output is measured by total output value in thousand rupiahs; while the inputs are: labour cost, cost of materials, cost of fuels, cost of electricity, and fixed capital cost. Results: This study uses data from the annual survey held by Statistics Indonesia of Central Java Province for the period of 2019. The LMMIs are divided into 24 different industrial classifications following the International Standard Industrial Classification of all Economic Activities (ISIC) Revision 4. Result shows that among 23 ISIC classifications, five of them are considered as efficient, they are: tobacco products; leather and related products and footwear; paper and paper products; coke, refined petroleum products, and electrical equipment. Limitations: This study is performed in a cross-sectional setting. It is recommended to conduct similar analysis in a panel data setting since more information of efficiency and changes in efficiency can be obtained. Contribution: Literature about assessing technical efficiency of manufacturing industry in Indonesia using SBM-DEA is quite limited; therefore, this study contributes to the literature by providing such analysis.